Development of Learning Video Media on Pattern Transfer Techniques to Fabric (TEKA) for Pattern-making Making Subjects - Asfia, Yunita; Yafie, Evania; Aini, Nurul; Krisnanda, Thiessa; Nasrillah, Yusrin (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
This study aims to develop and determine the feasibility of the TEKA (Technique for Transferring Patterns to Fabric) instructional video as a learning medium for the Pattern Making subject at SMK Negeri 7 Malang. The research employed a Research and Development (R&D) approach using the 4D development model (Define, Design, Develop, and Disseminate). The media was validated by subject matter experts and media experts and was tested on a limited scale involving 30 tenth-grade students from the Fashion Design and Production program at SMK Negeri 7 Malang. The validation results from subject matter experts showed an average score of 3.81, categorized as "Highly Feasible," with the material relevance aspect receiving a perfect score of 4.00. Media experts gave an average score of 3.66, with the highest rating on the operability aspect (3.71). The student trial yielded a satisfaction score of 85.7%, demonstrating that the media is suitable as an innovative tool for teaching pattern-transferring techniques onto fabric. The media effectively addressed students' difficulties in visualizing and transferring patterns from paper to fabric. Its strengths lie in the systematic presentation of material, flexible usage, and its function as both an independent learning tool and a classroom supplement. The study recommends regular content updates to align with industry developments and suggests developing similar media for other competencies. These findings emphasize the importance of technology-based media innovation in enhancing the quality of vocational education.